Standardising the Development of ODM Converters: The ODMToolBox. - Soto-Rey, I; Neuhaus, P; Bruland, Philipp; Geßner, S; Varghese, J; Hegselmann, S; Brix, T; Dugas, M; Storck, M (Stud Health Technol Inform)
CDISC's Operational Data Model (ODM) is a flexible standard for exchanging and archiving metadata and subject clinical data in clinical trials. The Portal of Medical Data Models (MDM-Portal) uses ODM to store more than 15000 medical forms. As not every electronic health system accepts ODM as input format, there is a need for conversion between ODM and other data standards and formats. This research proposes a standardised template-based process to develop ODM converters. So far, ten converters have been developed and integrated in the MDM-Portal following this process and new ones should be included soon. The template, programming utilities and an ODM test suite have been made online available and can be used to easily develop new converters.
Keywords: CDISC ODM; Semantics; interoperability